Streptococcus constellatus: a rare causative agent of pyogenic liver abscess. Issue 12 (18th December 2019) - Dsouza, Royson; Roopavathana, Beulah; Chase, Suchita; Nayak, Sukriya
Abstract : A 26-year-old man who was previously well presented to the emergency in septic shock. He had a preceding history of fever, right upper abdominal pain and jaundice. On examination, there was tenderness over the right hypochondrium and epigastrium, without features of generalised peritonitis. His blood tests were suggestive of sepsis with deranged liver function tests. CT scan of the abdomen showed multiples abscesses in various segments of the liver and a thrombus in the inferior venacava, without any other intraabdominal focus of infection. The abscess was aspirated under sonographic guidance, and the cultures grew Streptococcus constellatus species of S. milleri group (SMG). He received crystalline penicillin, based on culture sensitivity and underwent drainage of the abscess. There was a clinical improvement and he was subsequently discharged in a stable condition. On 3 months follow-up, there was a complete resolution of the liver abscess and normalisation of the liver function tests.